Clinical application of transcranial magnetic stimulation in multiple sclerosis - Zhou, Xiaoliang; Li, Kailin; Chen, Si; Zhou, Wenbin; Li, Jing; Huang, Qing; Xu, Tingting; Gao, Zhiyuan; Wang, Dongyu; Zhao, Shuo; Dong, Hao (Frontiers in Immunology, 2022)
Multiple sclerosis (MS) is a common chronic, autoimmune-mediated inflammatory and neurodegenerative disease of the central nervous system, the treatment of MS has enormous progress with the Disease-modifying drugs, but the complexity of disease course and clinical symptoms of MS requires the personalized treatment and disease management, including non-pharmacological treatment. Transcranial magnetic stimulation (TMS) is a painless and non-invasive brain stimulation (NIBS) technique, which has been widely used in neurological diseases. In this review, we mainly focus on the progress of physiological assessment and treatment of TMS in MS.